2015
DOI: 10.1248/cpb.c15-00369
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng Saponins in Different Parts of <i>Panax vietnamensis</i>

Abstract: Chemical and pharmacological studies of Panax vietnamensis (Vietnamese ginseng; VG) have been reported since its discovery in 1973. However, the content of each saponin in different parts of VG has not been reported. In this study, 17 ginsenosides in the different underground parts of P. vietnamensis were analyzed by HPLC/evaporative light scattering detector (ELSD). Their contents in the dried rhizome, radix, and fine roots were 195, 156, and 139 mg/g, respectively, which were extremely high compared to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 13 publications
1
16
0
3
Order By: Relevance
“…E (4.2 g). The structures of 1 – 12 were confirmed by comparison of LC/HR‐ESI‐MS data with those of reference ginsenosides identified by our groups in previous publications ( Figures S1 and S2 ) . The analysis was performed by UPLC‐QToF with the binary gradient elution system consisted of 0.1 % formic acid in water (A) and 0.1 % formic acid in acetonitrile (B).…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…E (4.2 g). The structures of 1 – 12 were confirmed by comparison of LC/HR‐ESI‐MS data with those of reference ginsenosides identified by our groups in previous publications ( Figures S1 and S2 ) . The analysis was performed by UPLC‐QToF with the binary gradient elution system consisted of 0.1 % formic acid in water (A) and 0.1 % formic acid in acetonitrile (B).…”
Section: Methodssupporting
confidence: 57%
“…In the previous study, we identified ginsenosides from the rhizomes and roots of VG . One of the most interesting characteristics that distinguish VG from the other Ginsengs is its remarkably high contents of ocotillol (OCT)‐type saponins with five‐ or six‐membered epoxy rings at C‐20, as compared with PPD and PPT‐type saponins . However, the antimelanogenic activity of OCT‐type saponins isolated from VG has not yet been investigated while that of some PPD and PPT ginsenosides had been evaluated .…”
Section: Introductionmentioning
confidence: 99%
“…Sâm ngọc linh (Panax vietnamensis) cùng chi Panax với nhiều loài sâm quý trên thế giới như sâm Panax ginseng (Hàn Quốc), Panax quinquefolius (Mỹ). Tuy nhiên, phân tích các hợp chất hóa học rễ củ sâm ngọc linh chứa tới 50 saponin (sâm triều tiên có khoảng 25 sanopin) và cập nhật những kết quả nghiên cứu mới nhất cho thấy danh sách saponin của sâm ngọc linh lên tới 52 loại (Duc et al, 1993(Duc et al, , 1994aLe et al, 2015). Ngoài những saponin đặc trưng như VR-3, 4, 8, 9, MR1 và MR2 (Duc et al, 1994b), sâm ngọc linh còn chứa một số saponin có dược tính cao đã được phát hiện trong các loài sâm khác cùng chi Panax như ginsenoside Rb1, Rg1, Rc, Rd hay Rg3 (Lee et al, 2016;Li et al, 2016Li et al, , 2017Tian et al, 2017;Sun et al, 2017;Gao et al, 2017) Các saponin này được cấu tạo từ các aglycon chính bao gồm protopanaxadiol (PPD), protopanaxatriol (PPT) và khung dammaran.…”
Section: Mở đầUunclassified
“…Kết quả phân tích thành phần MR2 -hoạt chất chính đặc trưng cho Sâm Việt Nam không thấy có trong khí sinh nhưng trong phần dưới mặt đất chiếm hàm lượng khá cao (từ 35 -42% hàm lượng saponin tổng số) và tăng dần theo thời gian trồng từ năm tứ 2 đến năm thứ 5, tương ứng đạt 2,23%, 3,26%, 4,54% và 5,75%, giảm ở năm thứ 6 (5,23%). Kết quả này hoàn toàn phù hợp với nghiên cứu của Nguyễn Thượng Dong và cộng sự [10] và Le et al, [3], các công bố đều cho thấy MR2 chiếm gần 50% hàm lượng saponin tổng số trong phần dưới mặt đất của và là hợp chất chủ yếu đặc trưng của SVN.…”
Section: Khảo Sát Sự Biến độNg Hàm Lượng Một Số Saponin-ginsenoside Tunclassified